Standardizing ovule age for in ovulo embryo rescue in seedless grape (Vitis vinifera) breeding under the subtropical region - AMOL KAILAS JADHAV; SANJAY KUMAR SINGH; MANISH SRIVASTAV; MAHENDRA KUMAR VERMA; AMOLKUMAR U SOLANKE; CHAVLESH KUMAR; NARENDRA SINGH (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during 2018–22 at ICAR-Indian Agricultural Research Institute, New Delhi to identify the appropriate ovule age (days after pollination-DAP) to rescue the in ovulo embryo after pollination in various seedless grape (Vitis vinifera L.) genotypes and their cross combinations. The research revealed that in in vitro ovule culture establishment, ovule maturity, and in ovulo embryo germination increased significantly from 18–33 DAP ovule age and declined thereafter from 33–43 DAP. The highest ovule culture establishment (85.17%), ovule maturity (71.38%), and in ovulo embryo germination (25.54%) and ovule growth (2.02 mm2) were consistently observed at 33 DAP ovule age in most of the grape genotypes and cross combinations. The time required for embryo germination was notably reduced at 33 DAP (105.24 days). The optimal ovule age for embryo rescue varied among different grape genotypes. It was noticed that 23 DAP ovule age is ideal for Centennial Seedless; 28 DAP for cross combination, Beauty Seedless × Pusa Urvashi; and 33 DAP for genotypes like Perlette, Beauty Seedless, Pusa Urvashi, Pusa Trishar, Pusa Aditi, Flame Seedless; and cross combination like Pusa Aditi × Beauty Seedless, Pearl of Csaba × Beauty Seedless, Pusa Urvashi × Perlette and Pusa Trishar × Perlette; and 38 DAP for Pusa Swarnika for maximum in ovulo embryo rescue and germination recovery under sub-tropics.